Serotonin‐release assay‐negative heparin‐induced thrombocytopenia. Issue 1 (6th November 2019) - Warkentin, Theodore E.; Nazy, Ishac; Sheppard, Jo‐Ann I.; Smith, James W.; Kelton, John G.; Arnold, Donald M.
Abstract: Heparin‐induced thrombocytopenia (HIT) is a prothrombotic drug reaction caused by platelet‐activating anti‐platelet factor 4 (PF4)/heparin antibodies. Pathogenic HIT antibodies can be detected by the serotonin‐release assay (SRA), a platelet activation test. We have regarded the SRA performed in our medical community ("McMaster" SRA) as having high sensitivity and specificity. Recently, the concept of "SRA‐negative HIT" has been proposed for enzyme‐immunoassay (EIA)‐positive/SRA‐negative patients with a HIT‐compatible clinical picture, who test positive in a PF4‐enhanced platelet activation assay. After identifying an index case of SRA‐negative HIT, we estimated the frequency of this condition by performing the "PF4‐SRA" (modified SRA using high concentrations of added PF4 rather than heparin) in EIA‐positive patients from a cohort study evaluating clinical and laboratory diagnosis of HIT. We defined SRA‐negative HIT as patients meeting three criteria: clinical picture compatible with HIT (4Ts ≥ 4 points); EIA‐positive (≥1.00 units); and PF4‐SRA‐positive. Among 430 patients, 35 were EIA‐positive/SRA‐positive and 27 were EIA‐positive/SRA‐negative. Among these 27 SRA‐negative patients, three were found to have subthreshold levels of platelet‐activating antibodies by PF4‐SRA, of whom one met clinical criteria for SRA‐negative HIT. Thus, based on identifying one patient with SRA‐negative HIT within a cohort study that found 35 SRA‐positive HIT patients, we estimate the sensitivity of the McMaster SRA for diagnosis of HIT to be 35/36 (97.2%; 95% CI, 85.8‐99.9%). Although the McMaster SRA is highly sensitive for HIT, occasional SRA‐negative but EIA‐positive patients strongly suspected of having HIT can have this diagnosis supported by a PF4‐enhanced activation assay such as the PF4‐SRA.